SLEEP QUALITY REVIEWED FROM PSYCHOLOGICAL WELL-BEING IN FINAL STUDENTS - Amelia, Vanisa Fitri; Khoiryasdien, Andhita Dyorita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
Sleep is one of the physiological needs that must be met by every human being. Changes in sleep patterns are generally caused by the demands of daily activities that result in a reduced need for sleep, so individuals tend to be hit by excessive sleepiness during the day. Sleep quality is affected by factors such as illness, exercise and fatigue, psychological stress, medication, nutrition, environment, and motivation. In previous studies, it was found that psychological well-being has a strong relationship with individual stress levels. This study aims to determine the relationship between psychological well-being and sleep quality in final students. The study used quantitative methods with a correlational approach. The study population consisted of final students who were taking 5th to 9th semesters of college. The sample taken consisted of 160 final students studying at universities in the Special Region of Yogyakarta. The sampling technique used is accidental sampling. The results of the correlation test using Pearson Product Moment with a value of p = 0.013 (P < 0.05) and a value of r = 0.196 showed a positive relationship between psychological well-being and sleep quality in final students. This means that the higher the psychological well-being, the higher the quality of sleep for the final student.